1982
DOI: 10.1111/j.1432-1033.1982.tb06514.x
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Inactivation of Lactoperoxidase Sensitized by Carbonyl Compounds

Abstract: 1. 2,3-Butanedione was found to be a poor noncompetitive inhibitor (Ki z 0.1 M) of bovine milk lactoperoxidase. Irradiation of an incubation mixture of these two substances in the visible region led, however, to an irreversible loss of enzyme activity. The inactivation rates were dependent on light intensity, light wavelength and sensitizer concentration. Maximal rate of inactivation occurred at 400 -420 nm. Other dicarbonyl compounds which caused a similar photodestruction of lactoperoxidase in the visible re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Estradioll7~-dehydrogenase of human placenta was reported to retain 22 residues of arginine per subunits buffer at pH > 8 in the dark [15]. However, a-chymotrypsin [16] and pepsin [17] in the absence of the borate ion, and aminopeptidase [18] and lactoperoxidase [19] in the borate buffer at neutral pH were inactivated by butanedione as a photosensitizing agent. The inactivation rate of the estradiol 17P-dehydrogenase by 16-oxoestrone under the laboratory illumination or ultraviolet light at 254 nm was the same as that in the dark.…”
Section: Discussionmentioning
confidence: 99%
“…Estradioll7~-dehydrogenase of human placenta was reported to retain 22 residues of arginine per subunits buffer at pH > 8 in the dark [15]. However, a-chymotrypsin [16] and pepsin [17] in the absence of the borate ion, and aminopeptidase [18] and lactoperoxidase [19] in the borate buffer at neutral pH were inactivated by butanedione as a photosensitizing agent. The inactivation rate of the estradiol 17P-dehydrogenase by 16-oxoestrone under the laboratory illumination or ultraviolet light at 254 nm was the same as that in the dark.…”
Section: Discussionmentioning
confidence: 99%
“…CPA) is a zinc metalloexopeptidase of 307 residues (MW = 34 472), and a well-studied enzyme (1)(2)(3)(4)(5)(6). This protease preferentially hydrolyzes peptide or ester bonds at the C-terminus of polypeptide substrates with hydrophobic (aromatic or aliphatic) residues.…”
Section: Introductionmentioning
confidence: 99%
“…Chromophore-sensitized photooxidation involves the intermediacy of singlet oxygen, and ketones have been shown to be effective sensitizers of photooxidation reactions of proteins (Mákinen & Mákinen, 1982a). Histidine and several other imidazole-containing compounds have been shown to be efficient quenchers of ketone-sensitized photooxidation (Mákinen & Mákinen, 1982b) of lactoperoxidase. As shown in Table IV,2.5 mM and larger concentrations of L-histidine were found to suppress the oxygen-stimulated nonspecific inactivation processes and to result in full protection by sodium cholate under aerobic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility for an oxygen-dependent photochemical reaction is chromophore-(dye) sensitized photooxidation (Means & Feeney, 1971). Mákinen & Mákinen (1982b) have recently made a survey of inhibitors of chromophore-sensitized photooxidation, and these workers have found that various histidine-type compounds are very efficient scavengers of the singlet oxygen that is believed to be the active oxidant in these reactions. In order to assess the importance of singlet oxygen in the aerobic inactivations, a study of the effect of L-histidine of the extent of inactivation and the protective effects of sodium cholate was made.…”
Section: Effects Of Oxygen and H-histidine On Photoinactivationmentioning
confidence: 99%